Centralization as the key survival benefit in acute neonatal surgery - Besendörfer, Manuel; Günster, Simone; Linz, Katja; Reutter, Heiko Martin; Diez, Sonja (Frontiers in Pediatrics, 2024)
Introduction: Centralization of neonatal surgical care for congenital malformations is already under discussion. Acute care of neonatal emergencies in perinatal centers with affiliated hospitals is not uniformly regulated in Germany. Materials and methods: Analyses are based on acute pediatric surgical care at four affiliated hospitals of a perinatal center. Epidemiologic data and outcome parameters “survival”, “intracerebral hemorrhage”, and “revision of surgical indication” are assessed. Comparison is made between patients receiving surgical treatment at affiliated hospitals (group A) and patients with transfer to the university center for therapy in case of surgical indication for gastrointestinal diseases (group B). Results: 17 group A-patients are compared to 40 group B-patients. Comparison of epidemiological data reveals no significant differences. There is a survival advantage with transfer to the university center (mortality of 29% in group A vs. 2% in group B, p = 0.007). Intracerebral hemorrhage occurred more frequently in externally treated patients (group A 24% vs. group B 2%, p = 0.024). Surgical indication was revised in 30% of group B at the university center (p = 0.011) with consecutive successful conservative treatment. Conclusion: Transfer of patients at the beginning of the acute phase of gastrointestinal diseases is key to optimize the quality of neonatal surgical care. However, larger population studies should confirm the presented results, discuss restricting factors of real care structures and should rule out bias in triage of patients.
CRIS-Team Scopus Importer:2024-04-05
Keywords: centralization; German medical system; neonatal emergency; neonatal surgery; perinatal center

Incisional hernia repair in a high-fidelity silicone model for open retro-muscular mesh implantation with preparation of the fatty triangle: validation and educational impact study - Zipper, C. T.; Friedrich, U.; Backhaus, J.; Koenig, S.; Mavroveli, S.; Wiegering, A.; Olbrecht, S.; Puppe, F.; Günster, Simone; Dietz, U. A. (Hernia, 2019)
Background: Incisional hernia repair requires detailed anatomic knowledge. Regarding median subxiphoidal hernias, the proper preparation of the fatty triangle is challenging. To foster proficiency-based training, a cost-efficient model for open median retromuscular mesh repair resembling the human body was developed, including the main anatomical structures related to the procedure. The aim is to create and validate a high-fidelity model on open retromuscular mesh repair suitable for "training before doing". Materials and methods: Different types of fabrics for imitation of connective tissue and 2-component silicones were used to construct the incisional hernia model. Sample size for validation of the model was determined by a triangular testing approach. Operations from six beginners and six experts were assessed by three blinded-raters. Reliability and construct-validity were evaluated on a behaviorally anchored rating scale (highest score: 4) for the criteria: “instrument use”, “tissue handling”, “near misses and errors”, and “end-product quality”. Results: The model authentically mimicked an open median retromuscular mesh repair. Participants considered the procedure realistic. Reliability was excellent, ranging from 0.811 to 0.974 for “end-product quality”, and “tissue handling“ respectively. Construct-validity was confirmed with experts significantly outperforming beginners in the “use of instruments” (Mbeg. = 2.33, Mexp. = 3.94, p < 0.001), “tissue handling” (Mbeg. = 2.11, Mexp. = 3.72, p < 0.001), “near misses and errors” (Mbeg. = 2.67, Mexp. = 3.67, p < 0.001), and “end-product quality” (Mbeg. = 2.78, Mexp. = 3.72, p < 0.001). Criterion-validity revealed a paradox effect: beginners performed significantly better than experts (p < 0.05) when preparing the fatty triangle. Conclusions: The model covers all relevant aspects involved in median-open retromuscular incisional hernia mesh repair. Performance differences between beginners and experts confirm construct-validity and thereby realism of the model. It enables to efficiently improve and practice technical skills of the demanding surgery.
CRIS-Team Scopus Importer:2019-12-17
Keywords: Fatty triangle; Incisional hernia repair; Retromuscular mesh repair; Simulation; Surgical model; Validation